A student solves the following equation:

Problem: 2(x−3)+3x=19
Step 1: 2x−6+3x=19
Step 2: (2x+3x)−6=19
Step 3: 5x−6=19
Step 4: 5x−6+6=19+6
Step 5: 5x=25
Step 6: x=5
What property justifies going from step 3 to step 4?

(1 point)
Responses

Addition Property of Equality
Addition Property of Equality

Combine Like Terms
Combine Like Terms

Substitution Property
Substitution Property

Commutative Property of Addition
Commutative Property of Addition

Distributive Property

1 answer

Addition Property of Equality